Magic school bus gets all dried up : a book about deserts. (New York : Scholastic, 1996)
Learn how plants and animlas survive in the desert.
From the episode of the animated TV series produced by Scholastic Entertainment Inc.
Keywords: Desert -- Juvenile literature; Children stories